REIMAGINING SOCIAL ENTREPRENEURSHIP THROUGH CREATIVE TECHNOLOGY: VIRTUAL INNOVATION FOR INCLUSIVE COMMUNITY DEVELOPMENT - Ira Ningrum Resmawa; Siti Masruroh; Paryadi Paryadi; Faisal Razak (Journal of Social Entrepreneurship and Creative Technology, 2026)
Digital transformation has reshaped the landscape of social entrepreneurship, offering innovative opportunities to address complex societal challenges. Traditional approaches often limit participation and fail to reach marginalized communities, highlighting the need for inclusive frameworks that leverage technology. Creative technological tools, including virtual platforms and collaborative digital solutions, present potential pathways to enhance engagement, co-creation, and equitable impact within social initiatives. This study aims to investigate how creative technology can be systematically integrated into social entrepreneurship to foster inclusive community development. Specific objectives include identifying mechanisms that enable participatory engagement, evaluating the impact of virtual innovation on social outcomes, and developing a conceptual framework to guide practitioners in implementing digitally-mediated social projects. A mixed-methods design was employed, combining quantitative surveys of 50 participants with qualitative interviews and case study observations. Data analysis involved descriptive statistics, inferential testing, and thematic coding to explore patterns of engagement, skill development, and social impact within technology-mediated interventions. Findings indicate that digital platforms significantly enhance participation, collaboration, and perceived community benefits. Engagement levels correlate with technological proficiency, while structured virtual co-creation processes foster empowerment and social cohesion. The study provides empirical and conceptual evidence that creative technology is a critical enabler of inclusive social entrepreneurship. These insights suggest practical guidelines for designing sustainable, scalable, and equitable digital interventions, advancing theoretical understanding of technology-driven social innovation.